Hardware implementation of the high frequency link inveter using the dSPACE DS1104 digital signal processing board - Salam, Zainal; Toh, Leong Soon; Ramli, Mohd. Zulkifli (2006)

(untitled)
In this paper, a detail description of a highly efficient and compact high frequency link inverter is given. The focus will be on the deadbeat controller implementation using the dSPACE DS1104 digital signal processing (DSP) board. In addition, other hardware components such as the gate drives, power circuit, control signals generation, signal conditioning and test-load banks is also described. Selected results from the experimental prototype will be presented.